A Preliminary Assessment of the Reproductive Performance of Nilotic Bucks under Intensive Management in the Semi-arid Climate of Khartoum (University of Khartoum Journal of Agricultural Sciences, 2023)
Three Nilotic bucks were fed sorghum-based diet and threemolasses-based diets to examine the effect of nutrition and seasons inKhartoum (Sudan) on the scrotal circumference, sexual behaviour andsemen quality. Reaction time was recorded in seconds from introductionto a goat in oestrus until ejaculation into an Artificial Vagina (AV). Thescrotal circumference was measured around the width of the two testiclesonce every month. Semen was collected by an AV at weekly intervals.Semen characteristics examined were volume of the ejaculate,spermatozoa motility and concentration. Although the Nilotic bucks didnot have a period of sexual quiescence, they had an active mating seasonstarting at the beginning of autumn as indicated by the improved semenquality and reaction time (22.8 and 17.0 sec in autumn and winter ascompared to 72.3 sec in summer). Testicular circumference reached itsmaximal size at the beginning of autumn (20.17 cm), remained at thislevel until mid-winter, and then declined thereafter and reached itsminimal value during the next summer (17.08 cm). The season affectedall semen characteristics examined and the best semen was obtained inautumn and winter. However, the magnitudes of these seasonal effectsmay not be sufficient to prevent the bucks from being used for breeding
Keywords: Feeding systems; scrotal circumference; season; semen; reaction time